Caracterización Económica y Productiva en pollos de carne Ross 308 en una Empresa Avícola Convencional de Mediana Producción en Moche - Luna Usquiano, Emeli Angela (2019)
The present investigation was carried out in the district of Moche, Province of Trujillo, La Libertad Region; with the objective of evaluating the production and profitability on the productive parameters in chickens line Ross 308. The records of closing of farm of 5 consecutive campaigns were used, counted with a total population of 1 891 907 birds, the following parameters were analyzed:% mortality first week,% accumulated mortality, average weight, food consumption, feed conversion index, type A, B, X, Y, kilos meat on sale, productive efficiency index (IEP) and benefit / cost ratio (B / C) ). The results were analyzed Excel vs 2013 and Spss vs 19. The results obtained in the analysis were the following: the amount of chicken encased is 28kg /2 at slaughter, The average of% mortality of first week is of 2.368%, the average of accumulated mortality% is of 7.28%, the average of the weights is of 2.658 kg to the 50 days of the bird, the average of consumption of food is of 4.8 kg / ave, the average of the alimentary conversion is 1.958, average chicken% A type 64.2%, chicken type B 29.48%, chicken type X 1.24%, chicken type Y 4.96%, average kilograms of meat on sale 186 035.93 kg, average IEP is 253.084, average cost ratio / benefit is 1.04. It is concluded that the productive and economic activity in meat chickens Ross 308, in a conventional poultry company in Moche, has no high profitability benefits.